KORELASI GENOTIPIK ANTARA HASIL DENGAN TINGKAT KETAHANAN TERHADAP PENYAKIT BERCAK DAUN HITAM PADA KACANG TANAH - , Yudiwanti; S. Sastrosumarjo; S. Hadi; S. Karama; A. Surkati; A. A. Mattjik (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1998)
A field evaluation was conducted to study the genotypic correlation between yield potentials and resistance level to the late leafspot of peanut. The experiment was carried out at Muara experimental-field from October 1994 to January 1995 using 100 genotypes with natural late leafspot inoculation. The result showed that the resistance level to late leafspot, wish was quantitatively reflected by the fresh-leaves percentage has negative genotypic correlation with total and filled-pod numbe1: The negative genotypic correlation were also found between resistance level and the weight of total pod, filled pod, as kernel, although not significant.